NICOTINE POUCHES AS A NEW CATEGORY OF SMOKE-FREE PRODUCTS: BETWEEN HARM REDUCTION POTENTIAL AND NEW PUBLIC HEALTH CHALLENGES - Skuza, Aleksandra Irena; Góral, Marta; Fidorowicz, Dominik; Sagan, Daniel; Sergiel, Katarzyna Helena; Siedlecki, Rafał; Torbacka, Emilia; Downar-Zapolska, Magda; Mikłaszewicz, Agnieszka; Bednarczuk, Katarzyna (International Journal of Innovative Technologies in Social Science, 2026)
Nicotine pouches (NPs) represent a rapidly growing category of tobacco-free, oral nicotine products, whose popularity stems from the perceived discretion of their use, the absence of combustion, and the belief that they pose lower health risks compared to cigarettes. The aim of this review article is to provide a comprehensive synthesis of current knowledge regarding the health, pharmacological, toxicological, behavioral, and population-level effects associated with the use of nicotine pouches. The scope of the study includes the chemical characteristics of the products, the presence of toxic substances, cytotoxicity and biological effects, implications for oral health, pharmacokinetics and acute physiological effects, patterns of use, risk perception, co-use with other nicotine products, as well as regulatory implications and public health significance.The evidence indicates that nicotine pouches contain significantly fewer harmful and potentially harmful ingredients than cigarettes, snus, or chewing tobacco, which supports their harm-reduction potential among adult smokers who completely replace combustible products with them. At the same time, they are not biologically inert. Local changes in the oral mucosa have been demonstrated, along with varied cytotoxic effects primarily associated with non-nicotine components, acute cardiovascular effects dependent on nicotine dose, and the risk of acute poisoning, particularly in children following accidental ingestion. Epidemiological studies also document the rapidly growing use of NPs among adolescents and young adults, frequent co-use with cigarettes and e-cigarettes, and the significant role of marketing and favorable risk perception in the popularization of these products.The available data suggests that the impact of nicotine pouches on public health is mixed: these products may serve as a harm-reduction tool for adult smokers, but at the same time, they may increase nicotine exposure among adolescents and people who have not previously used nicotine. The final balance of benefits and risks will depend on usage patterns, the level of market regulation, and the quality of future, independent, and long-term studies.